2018
DOI: 10.1111/wej.12355
|View full text |Cite
|
Sign up to set email alerts
|

A system for rapid and inexpensive treatment of sewage using the weed Eclipta prostrata in SHEFROL® bioreactor

Abstract: In a first report of its kind, it is shown that the weed Eclipta prostrata is able to treat sewage rapidly and effectively when used in the novel sheet‐flow‐root‐level (SHEFROL®) bioreactor developed earlier by the authors. Besides extensive primary and secondary treatment in terms of removal of suspended solids, chemical oxygen demand and biological oxygen demand, E. prostrata was also able to substantially remove the excess nutrients which cause eutrophication (nitrogen and phosphorous) and the heavy metals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Simulation results revealed that a high concentration of organic carbon will reduce oxygen migration in HF aerated wetland systems, thus reducing the treatment effect. Abbasi and Tauseef (2018) [18] reported a novel plate-flow-root horizontal bioreactor (SHEFROL (R)) on their own earlier development for the first time, hinting that the use of artemisoma annua can be used to treat wastewater quickly and efficiently. In addition to extensive primary and secondary treatments in the removal of suspended solids, chemical oxygen demand, and biological oxygen demand, E. prostrata is capable of substantially removing excess nutrients and heavy metals such as copper, nickel, and manganese leading to eutrophication (nitrogen and phosphorus); the system is expected to yield significant results in sewage treatment.…”
Section: Municipal Sewage Treatment Methodsmentioning
confidence: 99%
“…Simulation results revealed that a high concentration of organic carbon will reduce oxygen migration in HF aerated wetland systems, thus reducing the treatment effect. Abbasi and Tauseef (2018) [18] reported a novel plate-flow-root horizontal bioreactor (SHEFROL (R)) on their own earlier development for the first time, hinting that the use of artemisoma annua can be used to treat wastewater quickly and efficiently. In addition to extensive primary and secondary treatments in the removal of suspended solids, chemical oxygen demand, and biological oxygen demand, E. prostrata is capable of substantially removing excess nutrients and heavy metals such as copper, nickel, and manganese leading to eutrophication (nitrogen and phosphorus); the system is expected to yield significant results in sewage treatment.…”
Section: Municipal Sewage Treatment Methodsmentioning
confidence: 99%
“…On the basis of a series of studies [36,[38][39][40][41][42][43][44], employing different species of macrophytes which, in their natural habitats, exist either as free floating weeds or marshy plants rooted in soil, or as terrestrial species, the efficacy of the SHEFROL ® technology has been demonstrated. It has been seen that besides very efficient secondary treatment, which its main role, SHEFROL, also accomplishes significant levels of primary and tertiary treatment.…”
Section: The Potential Of Shefrol ® Technologymentioning
confidence: 99%